Worse becomes the worst: obesity inequality, its determinants and policy options in Iran - Toorang, Fatemeh; Amiri, Parisa; Djazayery, Abolghassem; Pouraram, Hamed; Takian, Amirhossein (Frontiers in Public Health, 2024)
• Inequality in obesity prevalence is reported in several high and low-income countries, including Iran. Obesity prevalence is disparate based on accommodation, gender, education, and other socioeconomic characteristics in Iran.• Obesity and inequality are linked through immediate and intermediate causes. Inequality in access to healthy foods, physical activity facilities, and health care is the immediate cause of this inequality. Of course, these immediate factors result from intermediate factors, including inequality against women, children, and refugees, and inequality in access to information and education, and financial resources.• Obesity control policies should pay more attention to the fundamental promotors of obesity inequality. Policymakers should implement equity-oriented obesity control policies such as taxing unhealthy foods, subsidizing healthy foods, providing healthy and free meals in schools, especially in disadvantaged areas, and providing nutrient-rich foods to low-income families. Also, environmental re-engineering to increase opportunities for physical activity, especially in marginalized and disadvantaged areas of the country, should be considered• . Declarations:We sincerely thank all stakeholders and experts who patiently participated in this long and time-consuming study. Unfortunately, we could not disclose their names to maintain confidentiality.The Ethics Committee of Tehran University of Medical Sciences approved the protocol of this project . All procedures in all phases of our study were performed following the ethical guidelines of the Tehran University of Medical Sciences. In addition, we followed the Chatham House Rule and did not report any data with participants' names.After explaining the aims and protocol of the study, informed consent was obtained from all participants. Permission was obtained to record the interview. They were assured that none of their comments would be published under their names and that no one but the original research team would have access to the interviews. They can leave the study at any time.